State Duma and Issues of Higher Education in Russia (1906-1917) - S. V. Darchieva (Научный диалог)
The aim of this research is to analyze the activities of the State Duma in Russia from 1906 to 1917, focused on reforming the higher education system. The research materials include stenographic reports of the State Duma during the specified period, normative documents, and memoir literature. The study reveals that the Duma of the early 20th century placed significant emphasis on issues related to the preparation of scientific and pedagogical personnel in higher education, increasing the number of universities, centralizing the management of universities, improving the financial situation of the faculty, and student rights. It is demonstrated that as a result of the active initiatives by the Duma, the budget of the Ministry of Public Enlightenment increased several times, and deputies supported legislative projects related to the opening of new universities, increasing state expenditures on higher education, and the development of culture and science. The legislative projects proposed by different Duma factions aimed at establishing a continuous connection between educational institutions at different levels. Representatives of the people advocated for the democratization of higher education. The amounts allocated for the training of professorial scholarship recipients, salary increases, pensions, and scholarships for teachers, professors, and students increased. The State Duma consistently and actively advocated for gender equality in obtaining higher education.